2019
DOI: 10.20319/pijtel.2019.31.98117
|View full text |Cite
|
Sign up to set email alerts
|

Esp Issue in Indonesian Tertiary Context: What Students Need in Learning English

Abstract: This study aims to analyze students' English needs in an ESP course. English for specific purposes has become a significant aspect in the learning process in Indonesian tertiary context. The significant of occupation requirement globally and the emergence of mastering certain skills for certain jobs drives the need of English for specific area. Referring to this concern, General English is considered no longer suitable and it should be specified into several subjects based on certain purposes. In this case, ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…It could lead to an assumption that the tasks prescribed in the coursebook or designed by the teachers required the students to work more on an individual basis or in groups. The importance of varying the types of class activities support [20], [49], [50]. The usefulness of pair work for students was found in [20], which revealed that students had a high preference for pair work activities.…”
Section: Discussionmentioning
confidence: 99%
“…It could lead to an assumption that the tasks prescribed in the coursebook or designed by the teachers required the students to work more on an individual basis or in groups. The importance of varying the types of class activities support [20], [49], [50]. The usefulness of pair work for students was found in [20], which revealed that students had a high preference for pair work activities.…”
Section: Discussionmentioning
confidence: 99%
“…Having this task, they work together to produce a similar sentence. Giving the students opportunity to have more tasks in joint construction can be a more meaningful possibility to develop their analytical thought writing a simple sentence in the same type of text Gestanti et al (2019a). The number of tasks can be determined according to the need of students.…”
Section: Organized Materialsmentioning
confidence: 99%
“…Thus, investigating the challenges of teaching ESP in higher education is vital because emergent issues can be used as a basis for proposing policies towards the improvement of ESP practices. Research on ESP has been primarily focused on investigating needs analysis in ESP curriculum or materials development (Aldohon, 2014;Bialik & Fadel, 2015;Boroujeni & Fard, 2013;Gass, 2012;Gestanti et al, 2019;Hou, 2013;Kazar & Mede, 2015;Kellerman et al, 2010;Özyel et al, 2012;Poedjiastutie & Oliver, 2017;Saragih, 2014;Serafini et al, 2015;Setiawati, 2016;Trisyanti, 2009). However, little has been done to reveal the evident challenges encountered by the ESP teachers.…”
Section: Introductionmentioning
confidence: 99%